Control of Movement of Metallic Particles in a GIS - Giri Prasad, A.; Upadhyay, Poonam; Suryakalavathi, M.; Karthik, N. (International Journal of Engineering and Technology, 2018)
The analysis of motion of metallic particles in a GIB along with a control strategy is presented in this work. Metallic particle contamination is an inevitable problem that greatly impairs the performance of dielectric medium (SF6 gas) in a GIS. This can lead to a catastrophic failure of a GIS. A CIGRE study suggests that more than twenty percent failures in a GIS are caused due to metallic particle contamination. The mathematical modeling is done for a GIB to find the electric field and movement of metallic particle in the Busduct. The movement of metallic particles depends mostly upon the local electric fields in the duct. The motion of a contaminating metal particle can be greatly decreased by coating the enclosure inner surface with a Dielectric material. The results are simulated and validated by using AM and CSM methods.Â